PENINGKATAN KETERAMPILAN MEMBACA MENULIS PERMULAAN MENGGUNAKAN MODEL VISUAL, AUDITORY, READ WRITE, KINESTHETIC DI KELAS II SD N 82/II DUSUN PANJANG - Guswita, Reni (Information Technology Education Department, 2022)
This research is a classroom action research, which consists of two cycles. Each cycle consists of planning activities, implementing actions, observing and reflecting. Data collection techniques in this study were observation, tests and documentation. The research subjects were 1 educator and 22 students. The results of this study showed the teaching learning process, the first meeting of the first cycle was 77%, the second meeting of the first cycle was 80%, the first meeting of the second cycle was 90%, the second meeting of the second cycle was 95.45%. Observation of students during the learning process in the first cycle of the first cycle of good category is still 0%, the second meeting of the cycle increased to 54%. Furthermore, the first meeting in the second cycle in the category increased to 77% and the second meeting in the second cycle in the good category increased to 91% which was said to be successful. The results of the initial reading and writing skills assessment of students in cycle I were in the good category of 12 people or 54%. In cycle II the good category increased to 20 people or 91% and was declared successful. Based on the results of this study, it can be concluded that the use of Visual, Auditory, Read Write, Kinesthetic models can improve students' initial reading and writing skills in class II.